Cleaning & sanitation in the food industry - Viscio, Rod; Rutigliano, Katrina; Video Education Australasia (Bendigo, Vic. : Video Education Australasia, 2009)
Throughout the program we look at various topics surrounding cleanliness and sanitisation in the food industry - why is cleanliness and sanitation so important, how to clean properly, food service industry cleaning, food manufacturing industry cleaning, storage and OH&S'--Container
Executive producer, Simon Garner
Presenter: Laura Kelly
DVD format
Keywords: Food industry and trade -- Sanitation; Food industry and trade -- Safety measures; Food service -- Sanitation